Android apps development for video processing - Quek, Shen An (Nanyang Technological University, 2023)
The rising trend of smartphone technologies and the increasing demand for video processing applications are closely related. Smartphones have seen significant advancements in recent years, with a rise in features such as more extensive and higher resolution screens, improved cameras and photography capabilities, faster processing speeds, and greater storage capacity. These advancements have enabled capturing and sharing of high-quality video content anywhere, anytime. With the rise of 5G networks, this video content can be shared and streamed faster and more reliably than ever. As a result, the demand for video processing applications has increased dramatically. These applications can easily compress, transcode, edit, and deliver video content to a wide range of devices and platforms. The growing use of video in various sectors, such as entertainment, education, marketing, and surveillance, further drives the demand for video processing applications.